Peran Organizational Citizenship Behavior Memediasi Iklim Organisasi terhadap Kinerja Pegawai - Rahmawati, Suci; Margiyanti Utami, Esti; Annisa, Nenden (Benefit: Jurnal Manajemen dan Bisnis, 2023)
Every organization or agency needs human resources to achieve its goals. In realizing these goals, performance is something that needs to be paid attention to by the organization or agency. Performance is related to several aspects such as organizational climate and organizational citizenship behavior. The purpose of this research is to test the influence of organizational climate on employee performance, test the influence of organizational climate on organizational citizenship behavior, test the influence of organizational citizenship behavior on employee performance, and test the influence of organizational climate on employee performance with organizational citizenship behavior as an intervening variable. The population in this study were Civil Servants of the Purworejo Regency Environment and Fisheries Service. The sampling technique in this research used saturated samples and a sample of 91 respondents was obtained. The data collection instrument uses a questionnaire and answers are assessed using a Likert scale. To determine the accuracy of the measurements and the stability of the questionnaire parameters, a validity and reliability test was first carried out. Data analysis using the SmartPLS 3.0 for Windows tool. The results of this research show that organizational climate has a positive effect on employee performance, organizational climate has a positive effect on organizational citizenship behavior, organizational citizenship behavior has a positive effect on employee performance, and organizational citizenship behavior mediates the effect of organizational climate on employee performance.